Development of Pencak Silat Teaching Materials Based on Google Sites for Eighth Grade Students at SMP Negeri 4 Bandar Lampung - Fiter Wijaya; Heru Sulistianta; Muhammad Rifaldo (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to produce learning media products in the form of pencak silat teaching materials based on Google Sites for eighth grade junior high school students and to describe the feasibility of these teaching materials. The method used in this study is the ADDIE development research method. The research procedure consists of five steps, namely analysis, design, development, implementation, and evaluation. This study was conducted at SMP Negeri 4 Bandar Lampung. Data collection techniques in this study included interviews, observations, and questionnaires. The results of the study were e-learning teaching materials based on Google Sites as teaching materials for pencak silat lessons. The teaching materials developed in this study were deemed suitable based on the results of validation and revision by subject matter experts with a percentage of 96%, language experts with a percentage of 90%, learning media experts with a percentage of 97.5%, physical education teachers with a percentage of 95%, small-scale student trials with a percentage of 90%, and large-scale student trials with a percentage of 89%. Therefore, it can be concluded that the e-learning teaching materials developed are suitable as PJOK teaching materials at SMP Negeri 4 Bandar Lampung.